Assembleia de Deus e teologia pública: o discurso pentecostal no espaço público - Majewski, Rodrigo Gonçalves (2010)
The current dissertation presents some topics of Pentecostal theology in interface with the concept of public theology, seeking to reflect on the possible consequences, in the public space, of a Pentecostalist based speech. The first part presents the more popular theology of the Assemblies of God, present in Sunday school magazines published by the publishing house of the denomination, CPAD. There has been a growing interest from this denomination in social and public issues, gradually expanding, even if not massively, the space dedicated to this topic, with a constant improving of the theological grounding. The second part also shortly explains some relevant topics of the Pentecostal theology of the Assemblies of God, which would be both applicable and enriching for the base of the relation between the believer, the church and the society from this theological school's point of view. The topics are the following: the power of the spirit (God's power) and the miracles; the ecclesiology; the sanctification and Pentecostalist ethics with its emphasis on the separation from the world; eschatology and its belief in the imminent return of Christ; and the notion of spiritual war and all pentecostal cosmology (belief in angels, demons and their influence on individuals, society and general reality). The third part asks about the public consequences that can be extracted from specific aspects of pentecostal theology. It talks, in a first moment, about how not to interpret. This could lead to inappropriate conducts for a Christian in the public space from the point of view of public theology. Subsequently this part suggests some readings that seem more adequate for the Pentecostal theology topics. It extracts from this theology desirable consequences in consonance to what some public theologians propose as a way of favoring the dialogue with society and promote a more effective participation in the public space in the search of a common good. This comes from the Pentecostal believer and the Assembly of God itself as an institution. Suggests the following interpretations: the power of god that summons humble community service to all society; a pilgrim church but aware and active; a burning expectation of the consummation of God's kingdom that motivates social transformation; a sanctification that spreads through society fighting injustice; and a humble and wise posture at the sight of spiritual phenomena that may influence people and society.